2002
DOI: 10.1093/oxfordjournals.rpd.a006087
|View full text |Cite
|
Sign up to set email alerts
|

226Ra, 228Ra and 228Th in Scale and Sludge Samples from the Campos Basin Oilfield E&P Activities

Abstract: More than 40 scale and sludge samples from the Campos Basin oilfield were analysed in terms of 226Ra, 228Ra and 228Th. Although the exact origin of the samples was not known, scale samples derived from production pipes and sludge samples from water-oil separation units. Reported values ranged from 0.13 to 331 kBq.kg(-1) for 226Ra, from 0.10 to 245 kBq.kg(-1) for 228Ra and <0.10 to 272 kBq.kg(-1) for 228Th in sludge samples. The concentrations in scales were much more regular than in sludges and ranged from 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…However, the concentra- tions of 226 Ra in scales measured in the present work are about one order of magnitude higher than in the study published by Beddow et al [19]. Conversely, these results matched up with those reported in other studies where scales formed in oil and gas industries were analyzed [20][21][22].…”
Section: Radiumsupporting
confidence: 82%
“…However, the concentra- tions of 226 Ra in scales measured in the present work are about one order of magnitude higher than in the study published by Beddow et al [19]. Conversely, these results matched up with those reported in other studies where scales formed in oil and gas industries were analyzed [20][21][22].…”
Section: Radiumsupporting
confidence: 82%
“…Table 3 shows the comparison of TENORM activity concentrations in worldwide scales, mainly from petroleum industry. Matta et al [23] found maximum concentrations of 93.2 kBq kg -1 for 226 Ra and 36.9 kBq kg -1 for 228 Ra, respectively, for scale samples from oil extraction units in the Campos Basin, Brazil (Table 3). However, the results obtained by Abo-Emagda et al [21] were quite higher for 226 Ra. In another study, Testa et al [24] found values up to 2.89 kBq kg -1 for 226 Ra in scales taken from pipes of the oil industry in Tunisia.…”
Section: Resultsmentioning
confidence: 99%
“…Due to differences in the chemical composition and density among ''black-powder'' samples and the standard solution used for the calibration of the system, a self-absorption correction was applied for the 210 Pb determination, as described by Godoy et al (1987). The 226 Ra and 228 Ra determination by gamma spectrometry was carried out as described by Matta et al (2002) and Godoy and Cruz (2003).…”
Section: Ra 228 Ra and 210 Pb Determinationmentioning
confidence: 99%